Psychological Flexibility With Prejudices Increases Empathy and Decreases Distress Among Adolescents: A Spanish Validation of the Acceptance and Action Questionnaire–Stigma - Valdivia-Salas, Sonsoles; Martín-Albo, José; Cruz, Araceli; Villanueva-Blasco, Víctor J.; Jiménez, Teresa I. (Frontiers in Psychology, 2021)
Empathy is an emotional response that may facilitate prosocial behavior and inhibit aggression by increasing empathic concern for others. But the vicarious experience of other’s feelings may also turn into personal distress when the person has poor regulation skills and holds stigmatizing beliefs. In thinking about the processes that may trigger the experience of personal distress or empathic concern, research on the influence of psychological in/flexibility on stigma is showing promising results. Both processes are assessed with the Acceptance and Action Questionnaire-Stigma (AAQ-S). The current study sought to carry out a validity study of a Spanish version of the AAQ-S with a sample of adolescents aged 11 to 17 years old. The study included an expanded test of its predictive validity with measures at three times to evaluate the role of psychological flexibility and inflexibility as risk or protective variables for the development of personal distress and/or empathic concern in the stigmatizer. Statistical analyses confirmed a two-correlated-factor solution, the adequate reliability of both factors, and their construct and predictive validity in the expected direction. The stigmatizer’s inflexible reaction to their stigmatizing thoughts predicted the occurrence of personal distress, whereas the stigmatizer’s flexible reaction to their stigmatizing thoughts predicted the occurrence of empathic concern for others. These findings confirm the importance of considering the role of regulatory skills in the experience of empathic concern or personal distress in the presence of stigmatizing thoughts, with possible implications for the promotion of prosocial behavior and the reduction of aggressive behavior among adolescents.